Jak zwracamy się do osób nieznajomych? Granica między swoim a obcym we współczesnej polszczyźnie - Kawamoto, Yumeko (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*74.66px); top: calc(var(--scale-factor)*286.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.04281);" role="presentation">The subject of this article is the manner of addressing strangers in Polish. In order <span dir="ltr" style="left: calc(var(--scale-factor)*75.21px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01257);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*84.88px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.967933);" role="presentation">verify the current use of the language in this regard, two research methods were used: a <span dir="ltr" style="left: calc(var(--scale-factor)*81.81px); top: calc(var(--scale-factor)*314.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00877);" role="presentation">survey method <span dir="ltr" style="left: calc(var(--scale-factor)*143.52px); top: calc(var(--scale-factor)*314.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991721);" role="presentation">and an analysis of comments on a <span dir="ltr" style="left: calc(var(--scale-factor)*279.00px); top: calc(var(--scale-factor)*314.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.969558);" role="presentation">website <span dir="ltr" style="left: calc(var(--scale-factor)*310.66px); top: calc(var(--scale-factor)*314.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991999);" role="presentation">aimed at the business com<span dir="ltr" style="left: calc(var(--scale-factor)*75.20px); top: calc(var(--scale-factor)*328.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988716);" role="presentation">munity. As the respondents of the survey indicated, the contemporary Polish language <span dir="ltr" style="left: calc(var(--scale-factor)*75.34px); top: calc(var(--scale-factor)*342.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00393);" role="presentation">speakers recognise the importance of the traditional border of officiality <span dir="ltr" style="left: calc(var(--scale-factor)*366.83px); top: calc(var(--scale-factor)*342.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01019);" role="presentation">when choos<span dir="ltr" style="left: calc(var(--scale-factor)*75.18px); top: calc(var(--scale-factor)*356.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03539);" role="presentation">ing the appropriate <span dir="ltr" style="left: calc(var(--scale-factor)*156.41px); top: calc(var(--scale-factor)*356.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00812);" role="presentation">forms of address. However, a <span dir="ltr" style="left: calc(var(--scale-factor)*277.71px); top: calc(var(--scale-factor)*356.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03446);" role="presentation">problem in communication <span dir="ltr" style="left: calc(var(--scale-factor)*392.79px); top: calc(var(--scale-factor)*356.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991354);" role="presentation">arises <span dir="ltr" style="left: calc(var(--scale-factor)*74.93px); top: calc(var(--scale-factor)*370.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02419);" role="presentation">when the conceptual opposition <span dir="ltr" style="left: calc(var(--scale-factor)*207.74px); top: calc(var(--scale-factor)*370.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00925);" role="presentation">of the official / unofficial intersects with the opposi<span dir="ltr" style="left: calc(var(--scale-factor)*75.21px); top: calc(var(--scale-factor)*384.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03012);" role="presentation">tion <span dir="ltr" style="left: calc(var(--scale-factor)*93.03px); top: calc(var(--scale-factor)*384.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.971321);" role="presentation">of ours / others. This problem is sometimes observed in a <span dir="ltr" style="left: calc(var(--scale-factor)*317.42px); top: calc(var(--scale-factor)*384.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.978695);" role="presentation">business conversation, in <span dir="ltr" style="left: calc(var(--scale-factor)*74.93px); top: calc(var(--scale-factor)*398.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.993308);" role="presentation">which a <span dir="ltr" style="left: calc(var(--scale-factor)*108.41px); top: calc(var(--scale-factor)*398.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00379);" role="presentation">recruiter addresses a <span dir="ltr" style="left: calc(var(--scale-factor)*192.66px); top: calc(var(--scale-factor)*398.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00448);" role="presentation">job candidate <span dir="ltr" style="left: calc(var(--scale-factor)*248.81px); top: calc(var(--scale-factor)*398.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.984864);" role="presentation">using Polish ty <span dir="ltr" style="left: calc(var(--scale-factor)*309.68px); top: calc(var(--scale-factor)*398.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999623);" role="presentation">form from the first contact <span dir="ltr" style="left: calc(var(--scale-factor)*75.34px); top: calc(var(--scale-factor)*412.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0113);" role="presentation">and treats them as a <span dir="ltr" style="left: calc(var(--scale-factor)*157.48px); top: calc(var(--scale-factor)*412.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0311);" role="presentation">person <span dir="ltr" style="left: calc(var(--scale-factor)*187.35px); top: calc(var(--scale-factor)*412.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.054);" role="presentation">on <span dir="ltr" style="left: calc(var(--scale-factor)*200.27px); top: calc(var(--scale-factor)*412.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.992702);" role="presentation">the “our” side. The analysis of the comments from the <span dir="ltr" style="left: calc(var(--scale-factor)*75.18px); top: calc(var(--scale-factor)*426.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999239);" role="presentation">internet showed that the relationship between the recruiter and the candidate <span dir="ltr" style="left: calc(var(--scale-factor)*381.74px); top: calc(var(--scale-factor)*426.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.959494);" role="presentation">basically <span dir="ltr" style="left: calc(var(--scale-factor)*75.16px); top: calc(var(--scale-factor)*440.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.97722);" role="presentation">remains between strangers and it is better to <span dir="ltr" style="left: calc(var(--scale-factor)*248.77px); top: calc(var(--scale-factor)*440.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.951238);" role="presentation">avoid the use of unofficial forms, especially <span dir="ltr" style="left: calc(var(--scale-factor)*75.21px); top: calc(var(--scale-factor)*454.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988684);" role="presentation">those which use the addressee's <span dir="ltr" style="left: calc(var(--scale-factor)*201.71px); top: calc(var(--scale-factor)*454.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988052);" role="presentation">first name.